Synthesis and characterization of pure and Nd-doped Bismuth Zinc Oxyborate (Bi2ZnOB2O6). (2017) - Harde, G.B.; Muley, G.G.
Abstract: Polycrystalline powder sample of Pure and Nd- doped bismuth zinc oxyborate (BZOB) having chemical formula Bi2 ZnOB2 O6 in xNd2 O3 -(1-x)Bi2 O-ZnO-2H3 BO3 ternary system (x=0 and 0.05) were synthesized. The solid state reaction method was used in two steps for synthesis. Powder samples were subjected to powder X-ray diffraction (XRD) analysis to confirm single phase. Second harmonic generation (SHG) study shows that the SHG effect has been increase for Nd doped material. This excellent property makes it potential for nonlinear optical as well as self frequency doubling laser device applications. Single crystal growth is in progress in our laboratory.